The Effectiveness of Constraint-Induced Movement Therapy versus Traditional Occupational Therapy on Upper Limb Function after Stroke - Zafar, Rimsha; Ahmad Khan, Usama; Usama, Muhammad; Khalid Attique, Muhammad; Siddiqui, Bakhtawar; Yousaf, Faraya (Journal of Health and Rehabilitation Research, 2023)
Background: Stroke significantly impacts upper limb function, necessitating effective rehabilitation strategies. Constraint-Induced Movement Therapy (CIMT) and Traditional Occupational Therapy (OT) are widely used, yet their comparative effectiveness in improving upper limb function remains to be fully established. Objective: The aim was to compare the effectiveness of CIMT and traditional OT in enhancing upper limb function in stroke survivors. The comparison was based on changes in the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) and the Stroke Impact Scale (SIS). Methods: This randomized clinical trial involved 40 adult stroke survivors, who were assigned to either CIMT (n=20) or traditional OT (n=20). Assessments using FMA-UE and SIS were conducted before and after the intervention. Data analysis was conducted using SPSS 22.0, included within-group and between-group comparisons using repeated-measures ANOVA and paired t-tests. Results: Both CIMT and traditional OT groups showed significant improvements in FMA-UE and SIS scores. The CIMT group's FMA-UE scores improved from a mean of 43.26 to 47.36 (p=0.006), and SIS scores from 43.99 to 49.03 (p=0.009). The traditional OT group displayed more substantial improvements, with FMA-UE scores increasing from 42.71 to 48.89 (p=0.001), and SIS scores from 44.31 to 50.04 (p=0.007). Between-group analysis revealed no significant differences at baseline, but post-intervention, traditional OT showed significantly better outcomes compared to CIMT. Conclusion: Both CIMT and traditional OT are effective in improving upper limb function and reducing stroke impact. Traditional OT, however, demonstrated a slightly greater improvement. These findings underscore the importance of incorporating diverse therapeutic approaches in stroke rehabilitation, tailored to individual patient needs.